A Decentralized Control Scheme for Grid-tied Cascaded-Type PV Inverter Systems - Li, Lang; Sun, Yao; Hou, Xiaochao; Fu, Siqi; Su, Mei (IEEE journal of emerging and selected topics in industrial electronics (Print), 2025)
This article proposes a decentralized control strategy for single-phase cascaded-type photovoltaic (PV) inverter systems operating in grid-tied mode. In the proposed scheme, one PV unit functions as a controlled current source, while the others act as voltage sources. Decentralized frequency synchronization is achieved, which is conducive to enhancing the system's reliability compared with the communication-based methods. In addition, the active power outputs for each PV unit, based on maximum power point tracking, are obtained. The proposed method exhibits a robust anti-disturbance capability, particularly under conditions of grid voltage amplitude and frequency variations. Furthermore, the stability of the proposed control is validated using the root locus method for grid-tied cascaded-type PV inverter systems. Finally, the performance and feasibility of the proposed decentralized control method have been validated by simulation and hardware-in-the-loop results.